Bank competition and credit risk in the Euro area, 2005-2017: Is there evidence of convergence? - Maria Karadima; Helen Louri (London School of Economics and Political Science (LSE), European Institute, 2020)
Consolidation in euro area banking has been the major trend post-crisis. Has it been accompanied by more or less competition? Has it led to more or less credit risk? In all or some countries? In this study, we examine the evolution of competition (through market power and concentration) and credit risk (through non-performing loans) in 2005-2017 across all euro area countries (EA-19), as well as core (EA-Co) and periphery (EA-Pe) countries separately. Using Theil inequality and convergence analysis, our results support the continued existence of fragmentation as well as of divergence within and/or between core and periphery with respect to competition and credit risk, especially post-crisis, in spite of some partial reintegration trends. Policy measures supporting faster convergence of our variables would be helpful in establishing a real banking union.
Keywords: 330; Banking competition; credit risk; NPLs; Theil index; convergence analysis